Geodesics and killing vector fields in a tangent bundle - Aydin Gezer,; Kursat Akbulut, (Penerbit ukm, 2006)
The main purpose of this paper is to study geodesics and Killing vector fields in a tangent bundle with respect to the synectic lift s∇ of an affine connection